ADAPTASI KOMUNIKASI ANTARA STRANGER DAN HOST CULTURE DI KOTA SEMARANG - Elvina Ghozali; Turnomo Rahardjo (Interaksi Online, 2019)
This study aims to describe the communication strategy carried out by ethnic Papuans to be able to interact with the host culture in Semarang. The method used in this research is a qualitative type with a phenomenology approach. This research is supported by co-cultural theory and minority group theory. The informants in this study consisted of five ethnic Papuan individuals who were conducting studies in the city of Semarang. The adaptation process that occurs between ethnic Papuan individuals and the host culture shows that there are conflicts in the form of differences in cultural values, prejudices, and superior vs. inferior positions among them. In this research, we can found several strategies used by each individual to be able to communicate with host culture, as a way for them to adapt in a new cultural environment. These informants applied several strategies such as opening themselves up, and socializing well. In addition, they also have learned the local language, changed their intonation, speaking style, and paid attention to non-verbal communication to be able to interact with the host culture. Communication that runs in depth and sustainably is also achieved by searching for host culture favorite topics, as well as mixing regional languages into the conversation. Differences in understanding culture also make ethnic Papuan individuals clarify, share stories and experiences about life in Papua, and ask for help from third party. These strategies are carried out by informants who aim to achieve accommodation, namely trying to get the host culture to accept their existence in the new environment. As a conclusion, it can be concluded that the application of a good strategy will create good communication, and can create a successful intercultural adaptation process.